ANALISIS EFEKTIVITAS PAJAK HOTEL DAN RESTORAN DAN KONTRIBUSINYA TERHADAP PENDAPATAN ASLI DAERAH KOTA SEMARANG - Zumroatun Akyuni, 08.0552.0028; Maryono, Maryono (Students Journal of Accounting and Banking, 2013)
The focus of this study will analyze the number of hotel tax and restaurant tax in the city of Semarang in 2006-2011. It also analyzes the development and effectiveness of hotel tax and restaurant tax in the city of Semarang in 2006-2011. The research sample is the data realization hotel tax, restaurant tax and the own local administration income in the city of Semarang period from 2006 to 2011. Collection method in this study using the documentation, where data obtained from the Bureau of Municipal Finance Semarang (DPKAD). The data analysis technique used in this study is a qualitative analysis. The test results are obtained that targets and realization hotel tax, restaurant tax and own local administration income of Semarang period of 2006 - 2011 has increased. The effectiveness of own local administration income deficit in 2006 and 2010. While the effectiveness of hotel tax and restaurant tax always increase the period 2006 to 2011. While the hotel and restaurant tax contributions to fluctuating own local administration income in 2006 and 2010. Contributions largest hotel and restaurant taxes in 2006 amounted to 31.41% in affecting own local administration income of Semarang. While the hotel and restaurant tax contribution to own local administration income is lowest occurred in 2011 at 17.27%.Keywords: effectiveness, hotel tax, restaurant tax, own local administration income